2001
DOI: 10.1038/35088000
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Ku heterodimer bound to DNA and its implications for double-strand break repair

Abstract: The Ku heterodimer (Ku70 and Ku80 subunits) contributes to genomic integrity through its ability to bind DNA double-strand breaks and facilitate repair by the non-homologous end-joining pathway. The crystal structure of the human Ku heterodimer was determined both alone and bound to a 55-nucleotide DNA element at 2.7 and 2.5 A resolution, respectively. Ku70 and Ku80 share a common topology and form a dyad-symmetrical molecule with a preformed ring that encircles duplex DNA. The binding site can cradle two full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

39
1,095
2
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,044 publications
(1,144 citation statements)
references
References 44 publications
39
1,095
2
8
Order By: Relevance
“…Structurally, Ku is unusual in that heterodimerization of the Ku70 and Ku80 subunits buries a large amount of surface area (~9000Å 2 [1]). Perhaps as a result of the extensive interfacial surface, we found that soluble Ku could not be produced by independently expressing the two subunits.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Structurally, Ku is unusual in that heterodimerization of the Ku70 and Ku80 subunits buries a large amount of surface area (~9000Å 2 [1]). Perhaps as a result of the extensive interfacial surface, we found that soluble Ku could not be produced by independently expressing the two subunits.…”
Section: Resultsmentioning
confidence: 99%
“…These data indicate that E. coli produced rKu is suitable for use in the biochemical analysis of mammalian NHEJ. Space-filling model of Ku showing Ku70 (red) and Ku80 (gold) generated using Protein Databank accession number 1JEY [1]. A) Side-view.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of the Ku70/80 heterodimer directly shows why this protein binds specifically to DNA ends: its ring shape allows it to thread onto a double-stranded DNA molecule, but not to internal DNA positions (Walker et al, 2001). As expected on the basis of this structure, the protein can slide along a DNA molecule to internal positions without the need for an energy source, such as ATP (de Vries et al, 1989;Ristic et al, 2003).…”
Section: Dna-pkmentioning
confidence: 91%